The Growth and Efficiency of Galah Shrimp Feed (Macrobrachium Rosenbergii De Man) with the Addition of Caffeine in Commercial Feed - Mahendra Mahendra; Muhammad Rizal (Budapest International Research in Exact Sciences (BirEx) Journal, 2019)
Galah shrimp (Macrobrachium rosenbergii de Man) was a high economic level fishery commodities. The efforts to increase productivity in galah shrimp cultivation can be done by applying efficiency the use of feed. One ingredient to reduce the large feed costs in feed production was from the type of caffeine compound. This study was aimed to analyze the dose of caffeine addition in the best feed on the growth and efficiency of shrimp feed. The method used was a completely randomized design experiment with 5 treatments and 3 replications. Caffeine levels used were 0; 0.5; 1; 1, 5; and 2 gr per kg of feed. The parameters observed were growth and feed efficiency. The results showed that the best addition of caffeine was P5 = 2 gr / kg of feed producing a specific growth rate of 0.0065; FCR 0.15 and EP 6.8. From the results of this study that the addition of caffeine in feed can have a positive effect on the observed parameters (P <0.05).